Peace in the minds: UNESCO, mental engineering and education - Poul Duedahl (FahrenHouse, 2020)
UNESCO - the United Nations Educational, Scientific and Cultural Organization - is often associated with its prestigious world heritage list. For a good reason. The list is undeniable the most popular initiative in the organization's entire history. But UNESCO is of course more than world heritage. It has over the years been preoccupied with a series of what appears to be extremely diverse topics, such as education for global citizenship, literary translation programs, copyright rules, nuclear power research and technical assistance to developing countries. But how exactly are the many different activities related to peace-making and mentality construction and what exact role does education play besides constituting the «e» in the organization's name? In order to answer that, I will bring the reader back to three unpretentious but rather important seminars that took place simultaneously in Paris at the beginning of the organization's existence, because I believe the subsequent projects they initiated embody what the employees at UNESCO initially defined as the organization's core tasks.